1988
DOI: 10.1007/bf00454494
|View full text |Cite
|
Sign up to set email alerts
|

The significance of hemarthrosis of the knee in children

Abstract: Diagnostic arthroscopy was performed in 40 consecutive patients under 16 years of age with hemarthrosis of the knee. The age of the patients ranged from 10 to 15 years, median 13.7 years. Eighteen patients had ruptures of the anterior cruciate ligament; seven ruptures were partial. Only two cases of fractures of the tibial spine were encountered. Seven patients had midsubstance tears of the anterior cruciate ligament. Eleven patients had patellar dislocations. Six patients had minimal capsular disruptions as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 9 publications
2
42
0
1
Order By: Relevance
“…The combination of an osteochondral fracture with an acute dislocation of the patella was believed to be uncommon before the availability of arthroscopy. Eiskjaer et al 9 performed 40 arthroscopic evaluations because of hemarthrosis and reported 3 (8%) osteochondral fractures. None of the fractures were detected on standard radiographs of the knee.…”
Section: Resultsmentioning
confidence: 98%
“…The combination of an osteochondral fracture with an acute dislocation of the patella was believed to be uncommon before the availability of arthroscopy. Eiskjaer et al 9 performed 40 arthroscopic evaluations because of hemarthrosis and reported 3 (8%) osteochondral fractures. None of the fractures were detected on standard radiographs of the knee.…”
Section: Resultsmentioning
confidence: 98%
“…Early reports" suggested that integrity of the ACL may be of minor importance in children but subsequent studies12"13 have found that ACL laxity can be troublesome. Eiskjaer et al 14 Many childrens' knee disorders are of unknown aetiology and are self limiting and only the presence of debilitating symptoms or unequivocal clinical features should justify operation without first using conservative measures. The difficulties in eliciting symptoms and signs make the idea of arthroscopy attractive but surgically treatable pathology is unusual and this makes excessive use ofthe technique questionable.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The true incidence of midsubstance ACL rupture in children is unknown, but ACL injury has been reported in 10% to 65% of pediatric knees with acute hemarthrosis. [8][9][10][11] Shea et al 12 found that ACL injuries accounted for 6.7% of total injuries and 30.8% of all knee injuries in soccer players aged 5 to 18 years in the United States. Bony ACL avulsions are more likely to occur in preadolescents, whereas adolescents are more prone to ACL substance tears.…”
mentioning
confidence: 99%